Meeting the challenge of human resource management a communication perspective - Miller, Vernon D.; Gordon, Michael E. (Routledge, 2014)
This book compiles readings by thought leaders in human resource management and communication, exploring the intersection of interests, theories, and perspectives from the two fields to highlight new opportunities for research and practice